Poeta, exsul, vates : a stylistic and literary analysis of Ovid's Tristia and Epistulae ex Ponto - Claassen, Jo-Marie (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Litt.) -- University of Stellenbosch, 1986.